Influence of the use of nurse sows on their lifetime performance - Kamila Pokorná; Jaroslav Čítek; Kateřina Zadinová; Monika Okrouhlá; Nicole Lebedová; Michal Komosný; Roman Stupka (Czech Journal of Animal Science, 2020)
Using nurse sows is a common practice for intensive pig farming because large numbers of piglets per litter result from intensive breeding. This aim of this study was to compare reproductive parameters of nurse sows and non-nurse sows in relation to subsequent reproductive performance. The study evaluated 463 breeding sows that produced at least one litter. The sows were divided into two groups: non-nurse sows (350 sows) and nurse sows (113 sows) at their first farrowing. The average length of first lactation was 35.12 days for nurse sows and 29.79 days for non-nurse sows. At first parity, nurse sows weaned 5.18% more piglets than did non-nurse sows (P < 0.05). At second parity, nurse sows had 2.25% more live born piglets than did non-nurse sows. Nurse sows also had 9.59% more total live born piglets and they were removed from the breeding herd later (on average by 67.1 days) than were non-nurse sows. In conclusion, using sows as nurse sows in their first lactations provides a good solution when there are large numbers of piglets per litter, and this practice has no negative effect on sows' subsequent reproductive performance.